Comparison of routine teaching with fishbowl and 1-min preceptor for dental undergraduate students: An interventional study - Shefalika Priyam; Roopali M Sankeshwari; Supriya Vyavahare; Anil V Ankola (Indian Journal of Dental Research, 2020)
Aim: To compare routine teaching method with fishbowl and a one-minute preceptor for undergraduate students. Objectives: 1. Evaluation of theoretical knowledge for WHO dentition status and treatment need by fish bowl and routine teaching. 2. Effectiveness of the combination of fish bowl and one-minute preceptor in understanding WHO dentition status and treatment need. Materials and Methods: This study was conducted on 38 third year undergraduate students, which was divided into two groups (Group A: Fishbowl, Group B: One-minute preceptor). Routine lecture for WHO dentition status and treatment need was taken, followed by baseline evaluation which was done by giving 10 sets of clinical images to students and asked them to give WHO score. Furthermore, fish bowl and one-minute preceptor method were performed and students were subjected with the same set of clinical images again. At the end of the session, feedback was taken from the students by means of five open-ended questions about their views on fish bowl and one-minute preceptor. Data were analyzed with SPSS version 20 (Chicago IL). Wilcoxon Sign Rank test and Mann Whitney 'U' test was performed for intragroup and intergroup comparison respectively. Results: Combination of fishbowl and one-minute preceptor shows statistically significant result over routine teaching method with P value of .000. Conclusion: Combination of Fish Bowl and OMP could be used for better teaching method for students, as the students are actively involved and more learning takes place; the deficiencies of one method would be compensated by the other.